Optimalisasi Perkembangan Kognitif Anak Usia Dini melalui Pola Asuh Orang Tua : Tinjauan Naratif - Dwi Anggun Lestari (Universitas Muhamadiyah Manado, 2026)
Cognitive development is an important aspect of early childhood growth because it forms the foundation for children’s abilities to think, remember, understand concepts, solve problems, and make decisions. Early childhood is often referred to as the golden age since development occurs very rapidly during this period, requiring appropriate stimulation from the surrounding environment, particularly the family. In this context, parents play a crucial role through the parenting styles they apply in daily life. This study aims to examine the relationship between parenting styles and early childhood cognitive development based on findings from previous research. The method used is a narrative review by analyzing relevant scholarly articles published between 2020 and 2026. Articles that met the inclusion criteria were then analyzed descriptively to identify the relationship between parenting styles and children’s cognitive development. The results of the review of 15 selected articles indicate that there is a significant relationship between parenting styles and early childhood cognitive development. Authoritative parenting emerged as the most consistently positive style, characterized by effective communication, emotional support, balanced supervision, and opportunities for children to develop independent thinking skills. Other factors, such as parents’ educational level, involvement in children’s learning activities, and a supportive learning environment, also contribute to cognitive development. In conclusion, authoritative parenting is considered the most effective approach in supporting optimal cognitive development in early childhood.